Immunological and bacteriological monitoring of periodontal tissue in pregnancy = Monitoreo inmunológico y bacteriológico de los tejidos periodontales en el embarazo - Solari, Natalia
We determine periodontal pathogens in periodontal pockets from pregnant women with periodontitis and associate it to the C reactive protein (CRP), nitrates, immunoglobulin A and G (Ig A and G), and myeloperoxidase (MPO) levels in saliva to identify some biomarkers as tools to predict the periodontal status from pregnant. The samples were obtained from periodontal pockets and saliva from 100 pregnant women (PW) and 50 non-pregnant women (NPW). Every patient was evaluated by: 1) probing depth (PD) and loss of clinical attachment level (CAL); 2) in saliva; CRP, MPO, Ig A and G) and nitrite concentrations, 3) in periodontal pockets: P.gingivalis, T.forsythia, T.denticola, P.intermedia, A.actinomycetemcomitans. InfoStat/P 2008 software was used with a p-value <0.05. Clinical parameters showed stages I and II of PD in both groups. P.intermedia and A.actinomycetemcomitans were observed only in periodontal pockets from PW. The CAL was higher in pregnant of the 3rd trimester than in the other stages and was associated with low levels of IgA and the presence of P.intermedia and T. forsythia in the same trimester. The levels of IgA in saliva would reflect the immunological situation in pregnant women. This could be used to monitor the immune status of the gingival tissues during pregnancy.